2016
DOI: 10.3389/fpls.2016.00958
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Global Acyl Lipid Metabolic Map by Comparative Genomics and Subcellular Localization Analysis in the Red Alga Cyanidioschyzon merolae

Abstract: Pathways of lipid metabolism have been established in land plants, such as Arabidopsis thaliana, but the information on exact pathways is still under study in microalgae. In contrast with Chlamydomonas reinhardtii, which is currently studied extensively, the pathway information in red algae is still in the state in which enzymes and pathways are estimated by analogy with the knowledge in plants. Here we attempt to construct the entire acyl lipid metabolic pathways in a model red alga, Cyanidioschyzon merolae, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…Nevertheless, for now it can be assumed that the pathways identified in higher plants [239][240][241] are on the whole followed in eukaryotic algae though, perhaps, in a simpler form with less genetic redundancy [31] (Figure 4). In an overall survey by comparative genomics and subcellular localisation, it was concluded that the pathways for acyl lipid metabolism in the unicellular red alga Cyanidioschyzon merolae were essentially similar to Arabidopsis [242].…”
Section: Glycerolipid Synthesismentioning
confidence: 99%
“…Nevertheless, for now it can be assumed that the pathways identified in higher plants [239][240][241] are on the whole followed in eukaryotic algae though, perhaps, in a simpler form with less genetic redundancy [31] (Figure 4). In an overall survey by comparative genomics and subcellular localisation, it was concluded that the pathways for acyl lipid metabolism in the unicellular red alga Cyanidioschyzon merolae were essentially similar to Arabidopsis [242].…”
Section: Glycerolipid Synthesismentioning
confidence: 99%
“…The chloroplast is the sole site of fatty acid synthesis in plants and algal cells (Mori et al 2016;Ohlrogge et al 1979;Somerville and Browse 1991), and this was considered a result of cyanobacterial endosymbiosis. Indeed, the accD gene encoding a subunit of prokaryotic acetyl-CoA carboxylase is encoded by the chloroplast genome of many plants and algae.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the desaturation of 18:0 does not take place in the plastid of C. merolae , as expected from the lack of stearoyl‐ACP desaturase. A previous study reported that a single KAS might be involved in the fatty acid synthesis in C. merolae plastid . In land plants, fatty acid synthesis involves three isoforms of KAS (KAS I/II/III) having different substrate specificities .…”
Section: Discussionmentioning
confidence: 99%
“…We then presented a hypothesis that Abbreviations ACP, acyl carrier protein; DAG, diacylglycerol; DGDG, digalactosyldiacylglycerol; ER, endoplasmic reticulum; FAME, fatty acid methyl ester; FFA, free fatty acid; G3P, glycerol 3-phosphate; the apparent differences in fatty acid composition in this alga and macrophytes could be understood in a common framework focusing on the role of plastid [1].Plastids are one of the major compartments of lipid metabolism in plants and algae, in which fatty acids and plastid membrane lipids are synthesized, such as monogalactosyldiacylglycerol (MGDG), digalactosyldiacylglycerol (DGDG), sulfoquinovosyldiacylglycerol (SQDG), and phosphatidylglycerol (PG) [8][9][10]. In plants, plastid is the sole site of long-chain fatty acid synthesis [11], and this is believed to be true for most algae [5,12,13]. The site of desaturation is, however, variable depending on fatty acids and double-bond position to be inserted.…”
mentioning
confidence: 99%
See 1 more Smart Citation